Объяснение:
24*(sin 15 - cos 15)/cos 30 = 24*( sin(60°-45°) - cos(60°-45°) ) /cos 30° =
Используем формулу: sin (x-y) = sin x * cos y - cos x * sin y
cos (x-y) = cos x * cos y + sin x * sin y
= 24* ( (sin 60 *cos 45 - cos 60 * sin 45) - (cos 60 * cos 45 + sin 60 * sin 45) ) /cos 30 = 24* (sin 60 *cos 45 - cos 60 * sin 45 - cos 60 * cos 45 - sin 60 * sin 45 ) /cos 30 = 24*( ) / = 24*( -) / = = = = =
Объяснение:
24*(sin 15 - cos 15)/cos 30 = 24*( sin(60°-45°) - cos(60°-45°) ) /cos 30° =
Используем формулу: sin (x-y) = sin x * cos y - cos x * sin y
cos (x-y) = cos x * cos y + sin x * sin y
= 24* ( (sin 60 *cos 45 - cos 60 * sin 45) - (cos 60 * cos 45 + sin 60 * sin 45) ) /cos 30 = 24* (sin 60 *cos 45 - cos 60 * sin 45 - cos 60 * cos 45 - sin 60 * sin 45 ) /cos 30 = 24*(
) /
= 24*( -
) /
=
=
=
=
= ![-8\sqrt{6}](/tpl/images/1331/6263/6e91c.png)